2020
DOI: 10.1080/00365521.2020.1829031
|View full text |Cite
|
Sign up to set email alerts
|

eHealth: Disease activity measures are related to the faecal gut microbiota in adult patients with ulcerative colitis

Abstract: After the first PCR (95°C for 3 min, 30 cycles of 95°C for 30 sec, 55°C for 30 sec, 72°C for 30 sec, and final extension at 72°C for 5 min), amplicons were purified with AMPure XP beads in a x0.8 sample-to-beads ratio. A second round of PCR (95°C for 3 min, 10 cycles of 95°C for 30 sec, 55°C for 30 sec, 72°C for 30 sec, and final extension at 72°C for 5 min) was carried out to add Illumina indexing primers, and libraries were purified with AMPure XP beads in a x1 sample-to-beads ratio. Finally, libraries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…isolated a polysaccharide from Ficus carica , which protected the goblet cells, elevated the expression of tight junction protein, suppressed the formation of proinflammation cytokines, and reformed the gut microbiome by enhancing the abundance of S24‐7 , Bacteroides , and Coprococus , and suppressing the abundance of Escherichia and Clostridium at the genus level [22] . Previous studies suggested that the properties of the intestinal microbiota in patients with UC were distinct from those in healthy individuals [23] . To further investigate RLP had a beneficial effect on the dysbiosis induced by canine ulcerative colitis, 16S rRNA sequencing data from fecal samples collected from different groups was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…isolated a polysaccharide from Ficus carica , which protected the goblet cells, elevated the expression of tight junction protein, suppressed the formation of proinflammation cytokines, and reformed the gut microbiome by enhancing the abundance of S24‐7 , Bacteroides , and Coprococus , and suppressing the abundance of Escherichia and Clostridium at the genus level [22] . Previous studies suggested that the properties of the intestinal microbiota in patients with UC were distinct from those in healthy individuals [23] . To further investigate RLP had a beneficial effect on the dysbiosis induced by canine ulcerative colitis, 16S rRNA sequencing data from fecal samples collected from different groups was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Previous studies suggested that the properties of the intestinal microbiota in patients with UC were distinct from those in healthy individuals. [23] To further investigate RLP had a beneficial effect on the dysbiosis induced by canine ulcerative colitis, 16S rRNA sequencing data from fecal samples collected from different groups was analyzed. The bacterial communities were tested by Venn diagram analysis (Figure 4A), which detailed the overlap and unique organisms between the OTUs in the fecal microbiota of each group.…”
Section: Rlp Optimizes the Structure Of Gut Microbiota In Dss-induced...mentioning
confidence: 99%
“…This profile, characterized by a high Proteobacteria/Firmicutes ratio, was also observed in mice receiving the least effective products from donors 1, 2, and 3 and positively correlates with colonic inflammation. Indeed, Proteobacteria, a phylum characterized by a high presence of endotoxin-bearing bacteria, is positively correlated with fecal calprotectin, an inflammation marker used in intestinal bowel disease (IBD) disease activity monitoring ( 68 ). Enrichment of bacterial genera associated with health benefits highlighted by a high Butycore index was also observed in mice treated with pooled product, while the results were heterogenous for mice treated with single donor-derived products.…”
Section: Discussionmentioning
confidence: 99%